2021
DOI: 10.1242/jeb.243129
|View full text |Cite
|
Sign up to set email alerts
|

Lens and cornea limit UV vision of birds – a phylogenetic perspective

Abstract: Most vertebrates have UV-sensitive vision, but the UV-sensitivity of their eyes is limited by the transmittance of the ocular media, and the specific contribution of the different media (cornea, lens) has remained unclear. Here we describe the transmittance of all ocular media (OMT), as well as that of lenses and corneas of birds. For 66 species belonging to 18 orders, the wavelength at which 50% of light is transmitted through the ocular media to the retina (λT0.5) ranges from 310 to 398 nm. Low λT0.5 corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Shortwave‐absorbing ocular filters are found in the lenses of diverse species across all major vertebrate groups examined, including fishes (Douglas & McGuigan, 1989; Siebeck & Marshall, 2000, 2001, 2007; Thorpe et al., 1993), humans (Kessel et al., 2010) and other mammals (Douglas & Jeffery, 2014), reptiles (Gower et al., 2019; Simões et al., 2016), birds (Lind et al., 2014; Olsson et al., 2021) and frogs (Yovanovich et al., 2019, 2020). However, we currently have little understanding of the forces driving the evolution of lens pigmentation in any group, and only recently have studies started to use phylogenetic comparative methods to investigate the evolution of this trait (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shortwave‐absorbing ocular filters are found in the lenses of diverse species across all major vertebrate groups examined, including fishes (Douglas & McGuigan, 1989; Siebeck & Marshall, 2000, 2001, 2007; Thorpe et al., 1993), humans (Kessel et al., 2010) and other mammals (Douglas & Jeffery, 2014), reptiles (Gower et al., 2019; Simões et al., 2016), birds (Lind et al., 2014; Olsson et al., 2021) and frogs (Yovanovich et al., 2019, 2020). However, we currently have little understanding of the forces driving the evolution of lens pigmentation in any group, and only recently have studies started to use phylogenetic comparative methods to investigate the evolution of this trait (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, we currently have little understanding of the forces driving the evolution of lens pigmentation in any group, and only recently have studies started to use phylogenetic comparative methods to investigate the evolution of this trait (e.g. Olsson et al., 2021; Yovanovich et al., 2020). To our knowledge, no study has found evidence for correlated evolution of lens transmission and any aspect of ecology.…”
Section: Introductionmentioning
confidence: 99%
“…This could occur through mixing at ocean front systems for instance [ 54 ], as sea-surface temperature gradients at frontal mixing zones can create dense cloud cover through accelerated atmospheric convection [ 55 ]. Manx shearwaters possess either violet sensitive (VS) or ultraviolet sensitive vision (UVS) [ 56 , 57 ]. Clouds don't attenuate these shorter wavelengths of light to the same degree as longer wavelengths in the visible spectrum [ 58 ], so complete cloud cover may not limit availability of Manx shearwater's visible spectra as much as we might expect.…”
Section: Discussionmentioning
confidence: 99%
“…Using sensory physiological studies to determine candidate stimuli for target species is an approach that allows for selection of targeted sensory stimuli and at a minimum helps to avoid implementing stimuli that cannot be perceived by the target animals ( Lim et al , 2008 ; Blumstein and Fernández-Juricic, 2010 ). For example, visual physiology and genetic research has shown that falcon and accipiter raptor eyes, including golden eagle eyes, filter out ultraviolet light and/or do not have ultraviolet-sensitive photoreceptors ( Doyle et al , 2014 ; Lind et al , 2014 ; Olsson et al , 2021 ), therefore making it unlikely that raptors would respond to ultraviolet light stimuli or deterrents ( Hunt et al , 2015 ; May et al , 2017 ). Similarly, we found sensory differences between the bald and golden eagles and between different types of sounds in noisy backgrounds, which collectively suggest that sound selection is important for development of effective alerting stimuli.…”
Section: Discussionmentioning
confidence: 99%